Enforcement of the creditor's claim rights in insolvency proceedings - Ulmane, Karlīna (Riga Graduate School of Law, 2023)
This paper focusses on Insolvency Law in Latvia, emphasizing its role as a protective mechanism for all involved parties and addressing the relevant issues in the context of statute of limitations. While the Insolvency Law acts as a shield that protects the creditors, this paper uncovers the challenges – loopholes and unaddressed issues – that could be causing a headache for some creditors. Creditors often navigate the complicated landscape of insolvency proceedings, encountering unexpected challenges as they attempt to protect their rights. This paper not only focuses on uncovering the problems at hand, but also provides possible outcomes and solutions for these problems. Nevertheless this paper will specifically look at the legal framework for enforcing creditors' claim rights, the difficulties creditors encounter, including prioritization, delays and potential conflicts, and the measures that have been put in place to make it simpler for creditors to recover money owing to them in insolvency proceedings.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Private law; insolvency law; creditor’s rights; Latvia